ANALISIS PENGARUH SURPLUS ARUS KAS BEBAS DEWAN KOMISARIS INDEPENDEN DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA DENGAN LEVERAGE SEBAGAI VARIABEL MODERATING (Survei Perusahaan Sub SektorTransportasi Yang Terdaftar Di BEI Periode 2015-2019) - Murwanti, Imawati Hari; Saptantinah, Dewi; Sunarti, Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Earnings management is a policy of accounting to achieve specific goals.The purpose of this research is to determine (1) the effect of free cash flow surpluson profit management (2) the influence of the independent board ofcommissioners on profit management (3) the influence of managerial ownershipon profit management (4) the effect of free cash flow surplus on leveraged profitmanagement as a moderation variable. The study used secondary data in the formof profit management data, free cash flow surplus, independent board ofcommissioners, managerial ownership and leverage. The population in this studywas a transportation sub-sector company registered with IDX during the period2015-2019. The sampling techniques in this study use purposive samplingtechniques. The data analysis techniques used are descriptive analysis, classicassumption test, multiple linear regression analysis and absolute difference testwith the results showing that free cash flow suplus has a significant impact onprofit management, independent board of commissioners and managerialownership has no effect on profit management. The results of the moderationvariable regression analysis with absolute differences indicate that leveragevariables moderate the relationship between free cash flow surplus to earningsmanagement.